A nanobiocatalytic system based on the self-assembly of ferrous phosphate with a high regioselectivity nitrile hydratase. (23rd December 2022) - Wang, Li; Huang, Jiao; Cui, Baocheng; Mu, Er; Liang, Changhai
Abstract: Our previous study identified a novel nitrile hydratase (NHase) with remarkable biotransformation activity towards adipamide during the production of 5-cyanovaleramide (5-CVAM), an important intermediate of herbicide and chemical raw material. Nevertheless, free NHase will face harsh conditions if they are applied directly in industrial processes. In this study, we, therefore, prepared Fe3 (PO4 )2 hybrid nanoflowers for NHase immobilization based on the protein-inorganic hybrid self-assembly by establishing a novel and facile method. The results showed that the NHase@Fe3 (PO4 )2 nanoflowers had significantly enhanced tolerance to the temperature ranging from 40 to 60°C when compared with free NHase. The catalytic activity of NHase@Fe3 (PO4 )2 nanoflowers remained high in extreme pH environments such as weak acid (pH 5) and strong alkali (pH 10) environments. In addition, the storage stability and reusability of encapsulated NHase were also superior to that of free NHase. NHase@Fe3 (PO4 )2 nanoflowers had a notable feature of high substrate tolerance. We found NHase@Fe3 (PO4 )2 nanoflowers still had 65% activity as the adiponitrile concentration increased up to 200 mmol L −1, whereas free NHase almost lost their catalytic activity when the adiponitrile concentration was just 100 mmol L −1 . All of these results clearly demonstrated that ferrous phosphate nanocrystals might offer a novel strategy for 5-CVAM production with nanobiocatalytic systems.